Grain boundary behavior of copper with C45 medium carbon steel - Dheeraj Varanasi; Peter Baumli (Resolution & Discovery, 2018)
Brazing is one of the most important techniques known in joining two similar/dissimilar metals/metal–nonmetal combinations for structural, mechanical, and aerospace applications. Brazing joints are formed by melting pure or alloyed foil called braze. Braze is melted in between the two substrates to be joined, and the joint is formed due to inherent adhesion and reactivity between braze and substrate. Copper and nickel are most commonly used brazes in the industry. Copper behavioral studies are mostly aimed at stainless steels (SS), and lot of research is carried out in Cu–SS systems. But, what is the copper behavior with medium carbon steels? What is the grain boundary behavior of copper and its mechanism when the alloying elements in steel are very low? Sandwich experiments were conducted with C45/Cu/C45 systems under an inert gas environment at 1100 °C. Cu was found to be wetting and penetrating the grain boundaries of medium carbon steel such as C45. The depth of penetration varied depending on holding times. The microstructure of the interface was characterized by SEM, and penetration depth was measured by image analysis software for better resolution and accuracy.